2008
DOI: 10.1016/j.febslet.2008.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals disorder of amino acid metabolism in four brain regions from a rat model of chronic unpredictable mild stress

Abstract: Chronic stress is closely linked to clinical depression, which could be assessed by a chronic unpredictable mild stress (CUMS) animal model. We present here a GC/MS-based metabolic profiling approach to investigate neurochemical changes in the cerebral cortex, hippocampus, thalamus, and remaining brain tissues. Multi-criteria assessment for multivariate statistics could identify differential metabolites between the CUMS-model rats versus the healthy controls. This study demonstrates that the significantly pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 50 publications
10
142
1
Order By: Relevance
“…The percentages of variance explained by the first and second components in the model are 23.6% and 16.0%, respectively. Variable importance in the projection (VIP) ranks the overall contribution of each variable (peak intensity) to the OPLS-DA model-variables with VIP > 1 were selected as differential signals [9] and [12]. Accordingly, we identified a total of 18 differential metabolites in our study using NIST library, and 11 of them were confirmed by standard compounds (Table 6).…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of variance explained by the first and second components in the model are 23.6% and 16.0%, respectively. Variable importance in the projection (VIP) ranks the overall contribution of each variable (peak intensity) to the OPLS-DA model-variables with VIP > 1 were selected as differential signals [9] and [12]. Accordingly, we identified a total of 18 differential metabolites in our study using NIST library, and 11 of them were confirmed by standard compounds (Table 6).…”
Section: Applicationmentioning
confidence: 99%
“…Therefore, tissue-targeted technology has considerable value since many diseases may cause detectable disturbances only to the local metabolic pathways within specific organs [11]. Tissue-targeted metabonomic analyses have been carried out on brain tissue [11][12][13], liver tissue [14][15][16], and kidney tissue [17][18][19]. Metabolite extraction is a critical step in tissue metabonomic study, and the chloroform-methanol-water solvent system is considered the preferred method in several reports [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The acquired MS files from the GC-TOF/MS analysis were exported in NetCDF format by ChromaTOF software (v3.3, Leco, St. Joseph, MI, USA). NetCDF files were processed by custom scripts in MATLAB (The Math Works, Natick, MA, USA) to carry out baseline correction, denoising, smoothing, alignment, time-window splitting, and multivariate curve resolution (Jonsson et al 2004(Jonsson et al , 2005Ni et al 2008). The resulting three-dimensional matrix (referred to as the metabolic matrix hereafter) includes sample information, peak retention time, and peak intensities.…”
Section: Methodsmentioning
confidence: 99%
“…VIP ranks the overall contribution of each variable to the OPLS-DA model, and those variables with VIP Ͼ 1.0 are considered relevant for group discrimination (29). Herein, VIP statistics and S-plot were applied to obtain the significant variables for subsequent metabolic pathway analysis (30,31). Besides the multivariate approaches, one univariate method, the Student's t test, was selected to measure the significance of each metabolite in separating HCC patients from healthy controls.…”
Section: Quantitative Analysis Of Bile Acids In Serum and Urine Samplmentioning
confidence: 99%